Allergen immunotherapy for pediatric asthma: current evidence and knowledge gaps. Issue 2 (April 2020) - Passalacqua, Giovanni; Landi, Massimo; Peroni, Diego G.
Abstract : Purpose of review: The introduction of high-quality and standardized extracts for immunotherapy has renewed the interest in the treatment of pediatric allergic asthma that represents a high-prevalence disease. Recent findings: In addition to clinical trials, several systematic reviews and metaanalyses were published, confirming overall the clinical efficacy of allergen immunotherapy in pediatric asthma. In addition, new data on the preventive effect of the treatment on asthma onset were published. Despite this, many intriguing questions emerged, in parallel to the development of knowledge. Summary: Allergen immunotherapy is overall effective for the treatment of asthma in children, but a class-effect should not be claimed, rather the efficacy of each single product. According to the recent findings, the challenge for the future research will be to clarify: when to start immunotherapy in children, which are (if they exist) the predictive biomarkers for efficacy in the single individual, the magnitude of the preventive effect and the optimal duration of the treatment.